Influence of reservoir cascades on sediment dynamics based on hydrosedimentological modeling: study of the Upper Paraguay river basin – Brazil - Oliveira, Warlen Librelon de; Pinheiro, Adilson (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
Water storage is crucial to optimize water resources, such as power generation, human supply, and flow regulation. Several studies analyze the influence of reservoirs on hydrosedimentological processes, highlighting environmental impacts and changes in the dynamics of watercourses. However, most of these studies focus on individual reservoirs, neglecting the cumulative effects of dams. This research aims to fill this gap by analyzing sediment dynamics in cascade reservoir systems. Five river basins in the Upper Paraguay river region were selected based on the presence of reservoirs, and the SWAT (Soil and Water Assessment Tools) model was used for hydrosedimentological modeling. It was observed that the creation of reservoir cascades significantly impacts sediment dynamics, with emphasis on retention in upstream reservoirs, especially in the largest ones. The location of reservoirs in the basins proved crucial in modifying sediment transport along watercourses. Furthermore, we observed changes in the spatial distribution of sediment production, with inversion of patterns in some cascades. The simulations provided a detailed understanding of sediment behavior, providing important support for managers in making decisions about the installation of new hydroelectric plants, going beyond traditional environmental impact studies.